The Efficacy and Safety of Immune Checkpoint Inhibitors in Patients With Cancer and Preexisting Autoimmune Disease - Tang, Hui; Zhou, Jianfeng; Bai, Chunmei (Frontiers in Oncology, 2021)
Immune checkpoint inhibitor (ICI) is a revolutionary breakthrough in the field of cancer treatment. Because of dysregulated activation of the immune system, patients with autoimmune disease (AID) are usually excluded from ICI clinical trials. Due to a large number of cancer patients with preexisting AID, the safety and efficacy of ICIs in these patients deserve more attention. This review summarizes and analyzes the data regarding ICI therapy in cancer patients with preexisting AID from 17 published studies. Available data suggests that the efficacy of ICIs in AID patients is comparable to that in the general population, and the incidence of immune-related adverse events (irAEs) is higher but still manageable. It is recommended to administer ICIs with close monitoring of irAEs in patients with a possibly high benefit-risk ratio after a multidisciplinary discussion based on the patient’s AID category and severity, the patient’s tumor type and prognosis, alternative treatment options, and the patient’s intention. Besides, the prevention and management of irAEs in AID patients have been discussed.